Spontaneous variability analysis for characterizing cardiovascular responses to water ingestion - Nozawa, M.; Yana, K.; Kaeriyama, K.; Mizuta, H.; Ono, T. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2009)
This paper examines the effect of water ingestion on the cardiovascular system, utilizing advanced fluctuation analysis. The ingestion of water has been known to significantly raise the blood pressure in subjects with autonomic disorders, resulting in the effect of preventing syncope occurrences. For precise characterization of the effect of water ingestion, head-up tilt experiments at 80 degrees have been conducted for fourteen healthy subjects, ranging in age from 16 to 24. Systolic/diastolic blood pressures (sBP/dBP), total peripheral resistance index (TRPI) and ECG RR intervals (RRIs) were measured for thirty minutes before and after the isotonic water ingestion of 340 ml. Blood pressures: sBP (2.8%), dBP(3.6%), and TPRI (5.3%) showed statistically significant increases after the water ingestion. RRIs also tended to increase (2.3%), although they were not statistically significant. The data analysis confirmed that the water injection of 340 ml has the acute effect against the syncope occurrences that are mainly due to the increase in TPRI. Then heart rate (HR) spectral analysis with the derivative of the cubic spline interpolation (DCSI) method, and a closed loop system identification technique, which associate fluctuations in sBP and HR, are utilized for further precise characterization of the change in recorded physiologic quantities.